Recalcitrant Issues and New Frontiers in Nano-Pharmacology - Bhardwaj, Vinay; Kaushik, Ajeet; Khatib, Ziad M.; Nair, Madhavan; McGoron, Anthony J. (Frontiers in Pharmacology, 2019)
Packaging of old pharma drugs into new packaging “nanoparticles” is called nano-pharmacology and the products are called nano-based drugs. The inception of nano-pharmacology research and development (R&D) is marked by the approval of the first nano-based drug Doxil® in 1995 by the Food and Drug Administration. However, even after more than two decades, today, there are only ~20 nano-based drugs in the market to treat cancers and brain diseases. In this article we share the perspectives of nanotechnology scientists, engineers and clinicians on the roadblocks in nano-pharmacology R&D. Also, we share our opinion on new frontiers in the field of nano-pharmacology R&D that may allow rapid and efficient transfer of nano-pharma technologies from R&D to market.